2003
DOI: 10.1097/00003226-200303000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Keratitis Caused by an Unusual Fungus, Phoma Species

Abstract: Phoma species, though rarely pathogenic to humans, may cause keratitis in some patients. To our knowledge, this is the first well-documented case of Phoma keratitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…15 Although not seen in all cases, one of the clinical features of the keratitis caused by dematiaceous fungi is pigmented infiltrate. [8][9][10][11][12] We report the clinical, microbiological, and histopathologic features of this unique presentation, which has not been described in the literature. We also made an attempt to correlate clinical features with histopathologic findings to understand its pathogenesis and the clinical significance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Although not seen in all cases, one of the clinical features of the keratitis caused by dematiaceous fungi is pigmented infiltrate. [8][9][10][11][12] We report the clinical, microbiological, and histopathologic features of this unique presentation, which has not been described in the literature. We also made an attempt to correlate clinical features with histopathologic findings to understand its pathogenesis and the clinical significance.…”
Section: Discussionmentioning
confidence: 99%
“…A small proportion of cases, however, shows brown to black macroscopic pigmentation of the corneal infiltrate. [8][9][10][11][12] In the series reported by Garg and associates, 27% of cases of dematiaceous fungal keratitis presented with pigmented lesions. 9 When we examined cases with pigmented infiltrate we found that this presentation is characterized by a dry raised infiltrate, resembling a plaque, with a brown to black pigmentation on its surface.…”
mentioning
confidence: 99%
“…Phaeohyphomycosis caused by Phoma has been sporadically described in the literature. Most reported cases are subcutaneous and ocular infections . Systemic infection with Phoma spp.…”
Section: Black Fungal Species With Clinical Relevancementioning
confidence: 99%
“…Cite this article as Cold Spring Harb Perspect Med 2015;5:a019570 including subcutaneous infection, keratitis, or onychomycosis that are traumatically acquired (Arrese et al 1997;Zaitz et al 1997;Rishi and Font 2003;Errera et al 2008;Tullio et al 2010). Phoma species produce colonies with spherical, solitary dark pycnidia, usually each with a single or sometimes with several ostioles.…”
Section: Black Molds and Yeasts Pathogenic To Humansmentioning
confidence: 99%